The merger and assembly histories of Milky Way- and M31-like galaxies with TNG50: disc survival through mergers - Sotillo-Ramos, Diego; Pillepich, Annalisa; Donnari, Martina; Nelson, Dylan; Eisert, Lukas; Rodriguez-Gomez, Vicente; Joshi, Gandhali D.; Vogelsberger, Mark; Hernquist, Lars (Monthly notices of the Royal Astronomical Society, 2022)
We analyse the merger and assembly histories of Milky Way (MW) and Andromeda (M31)-like galaxies to quantify how, and how often, disc galaxies of this mass can survive recent major mergers (stellar mass ratio ≥ 1:4). For this, we use the cosmological magneto-hydrodynamical simulation TNG50 and identify 198 analog galaxies, selected based on their z = 0 stellar mass ($10^{10.5-11.2}\, \rm {M}_{\odot }$), discy stellar morphology and local environment. First, major mergers are common: 85 per cent (168) of MW/M31-like galaxies in TNG50 have undergone at least one major merger across their lifetime. In fact, 31 galaxies (16 per cent) have undergone a recent major merger, i.e. in the last 5 Gyr. The gas available during the merger suffices to either induce starbursts at pericentric passages or to sustain prolonged star formation after coalescence: in roughly half of the cases, the pre-existing stellar disc is destroyed because of the merger but reforms thanks to star formation. Moreover, higher merger mass ratios are more likely to destroy the stellar discs. In comparison to those with more ancient massive mergers, MW/M31-like galaxies with recent major mergers have, on average, somewhat thicker stellar discs, more massive and somewhat shallower stellar haloes, larger stellar ex situ mass fractions, but similarly massive kinematically defined bulges. All this is qualitatively consistent with the different observed properties of the Galaxy and Andromeda and with the constraints on their most recent major mergers, 8-11 and 2 Gyr ago, respectively. According to contemporary cosmological simulations, a recent quiet merger history is not a pre-requisite for obtaining a relatively thin stellar disc at z = 0.